Technology alternatives to recover the vegetation coverage in the Rubiales, Puerto Gaitán-Meta (Revista Sistemas de Producción Agroecológicos, 2014)
The objective of this study was to validate and apply methodologies for evaluation and development of technologies for the restoration of soils affected by the oil company "Rubiales" through fitting models or arrangements involving practices and conservation tillage systems and the use of species herbaceous, shrub and tree, which plant materials were selected, with rapid growth potential and continuing to contribute to the recovery of permanent vegetative cover. Agronomic management practices and conservation tillage systems for intervention revegetation processes in order to return to areas covered with vegetation of Puerto Gaitan, located on colombian altillanura simultaneously making technology transfer to users and producers of this area is also defined. The partial incorporation of inputs and sources of phosphorus as calfos in the process of setting practices of establishment, were successful in areas that were again covered by vegetation, improving the supply or availability of nutrients to plants at different stages development. Selected forage materials were: B. decumbens, B. dictyoneura and B. humidicola, demonstrated adaptation to soil and climatic conditions of the area. Early fertilization lots with soluble sources, can help counteract negative effects on runoff seedlings, because if a quick and vigorous development of these accomplished, the anchor and higher plant population per unit area is increases; considering the moment of fertilization, which should be conducted between 30 to 45 days after planting. However, this work is determined by the moisture conditions associated with precipitation in areas that were again covered by ground vegetation. With the practices used and the use of these three species timely delivery of various lots within 120 days with 70% criterion of minimum coverage was achieved, demonstrating adaptation to soil and climatic conditions of the area.
Keywords: recovery of soils; vegetation; grasses